2020
DOI: 10.1093/humrep/deaa103
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging classification of deep pelvic endometriosis: description and impact on surgical management

Abstract: Abstract STUDY QUESTION Is an MRI classification of deep pelvic endometriosis (DE) able to correctly predict the risk of DE surgery. SUMMARY ANSWER A new radiological classification, that we have called the deep pelvic endometriosis index (dPEI) classification, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 27 publications
2
32
0
3
Order By: Relevance
“…Recent literature has also evaluated inter-reader agreement with this classification, showing varying results; Thomassin-Naggara et al’s trial (2020) consisted of 150 cases affected by DIE. They found excellent inter-reader agreement for A and C compartments but poor agreement for the B compartment, in accordance with previous publications by Saba et al (2010) and Bazot et al (2011) [ 29 , 30 , 31 ]. On the other hand, the recent trial conducted by Burla et al (2020), which consisted of 21 cases of DIE, showed an overall lower concordance, with a particularly weak inter-rater agreement for compartment C [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Recent literature has also evaluated inter-reader agreement with this classification, showing varying results; Thomassin-Naggara et al’s trial (2020) consisted of 150 cases affected by DIE. They found excellent inter-reader agreement for A and C compartments but poor agreement for the B compartment, in accordance with previous publications by Saba et al (2010) and Bazot et al (2011) [ 29 , 30 , 31 ]. On the other hand, the recent trial conducted by Burla et al (2020), which consisted of 21 cases of DIE, showed an overall lower concordance, with a particularly weak inter-rater agreement for compartment C [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Eligibility criteria included women aged between 18 and 50 years, with one or more deep endometriotic nodules defined as infiltration greater than 1.5 cm in diameter, equivalent to grade 2 (invasion 1 e 3 cm) or grade 3 (invasion >3 cm) of the ENZIAN classification (Thomassin‐Naggara et al, 2020) evaluated with magnetic resonance imaging. Although deep endometriosis is defined as infiltration for more than 0.5 cm, we included only cases with more than 1.5 cm to minimize false‐positive imaging diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Di Paola et al ( 2015 ) and Burla et al ( 2019 ) compared MRI findings with surgical findings using the Enzian classification and found good agreement between surgical and MRI Enzian classifications. Thomassin-Naggara et al ( 2020 ) showed that the Enzian classification based on MRI findings is reproducible and correlates with surgical findings. Their retrospective observational study included 150 patients with DE that underwent MRI and subsequent surgery.…”
Section: The Enzian and (#) Enzian Classificationsmentioning
confidence: 99%